10.19105 - Zulkarnayn, Diki; Thoha, Mohammad (IAIN Madura, 2021)
The implementation of Internet-Based Islamic Education Learning at SMAN 1 Pamekasan feels increasingly needed to be used as an alternative in fostering students' motivation and enthusiasm for learning, especially PAI learning. This study aims to examine teachers and students in innovating internet-based PAI learning, the obstacles experienced by teachers and students in implementing internet-based PAI learning, and also the implications of internet-based PAI learning at SMAN 1 Pamekasan. The focus of research in this study are: (1) How is the implementation of Internet-based PAI learning media at SMAN 1 Pamekasan? (2) What are the barriers to Internet-based PAI learning at SMAN 1 Pamekasan? (3) What is the solution to the obstacles to Internet-based PAI learning at SMAN 1 Pamekasan? This study uses a qualitative approach which intends to understand the phenomenon of what is experienced by the research subject. Data collection techniques carried out by researchers are interviews, non-participant observations, and documentation of a number of related sources. Data analysis during the research and after the research took place using data reduction, data presentation, and data verification for field studies. The results of the study indicate that: First, the implementation of internet-based PAI learning at SMAN 1 Pamekasan is quite adequate and is highly responded to by the principal, teachers, especially students. Although not 100% but with internet-based PAI learning, it is easy for teachers and students to carry out learning in class, which was originally boring to be fun and more efficient. Students who miss lessons can directly access learning by using the internet. Second, obstacles. Internet-based PAI learning at SMAN 1 Pamekasan is by providing training to PAI teachers regarding the implementation of internet-based learning, so that teachers who are less able to operate the internet can be helped by other PAI teachers. Third, student learning solutions and the use of internet-based PAI learning implementation at SMAN 1 Pamekasan, can be seen from the activeness of students in class and the results of student evaluations. To the principal of SMAN 1 Pamekasan for always providing support to teachers, especially PAI teachers related to internet media for the advancement of education at SMAN 1 Pamekasan. This support is by involving teachers in workshops or training on the implementation of internet-based PAI learning. Kata Kunci: Pembelajaran PAI, Berbasis Internet